PENGEMBANGAN MODUL AJAR BERORIENTASI ESD PADA MATERI HEMAT ENERGI DI KELAS VI SEKOLAH DASAR - Hikmah, Putri Durrotul; Suratmi, Suratmi (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
This research aims to evaluate the quality of ESD (Education for Sustainable Development) oriented teaching modules on energy saving material in class VI elementary school which were developed to support the teaching and learning process. The main issue faced is the lack of valid and effective ESD-oriented teaching modules used by teachers. This research offers a solution by developing teaching modules using research and development methods based on 4D models (Define, Design, Develop, Disseminate). Expert first validation showed 96,1% results in the